(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
In a multitenant cloud environment, securing data access is a critical concern due to the shared nature of resources among multiple users. Traditional security methods often fall short in addressing the unique challenges posed by such environments. This paper explores the role of Multi-Factor Authentication (MFA) and encryption in enhancing data security for cloud resources in multitenant settings. MFA adds an additional layer of security by requiring multiple forms of verification before granting access to cloud resources, while encryption ensures that data remains protected both in transit and at rest. The combination of these two security mechanisms can significantly reduce the risk of unauthorized access and data breaches. This paper also reviews various encryption algorithms and MFA techniques employed in cloud security, analyzes their effectiveness, and proposes an integrated approach to securing data access. The findings indicate that a hybrid model involving both MFA and encryption provides a robust solution for securing cloud resources in multitenant environments, addressing both internal and external threats effectively.